Ion desorption from molecules condensed at low temperature: A study with electron-ion coincidence spectroscopy combined with synchrotron radiation - Mase, Kazuhiko; Nagasono*, Mitsuru; Tanaka**, Shin-ichiro; Sekitani, Tetsuji; Nagaoka, Shin-ichi (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
This article reviews our recent work on photo-stimulated ion desorption (PSID) from molecules condensed at low temperature. We have used electron-ion coincidence (EICO) spectroscopycombined with synchrotron radiation. The history and present status of the EICO apparatus is described,as well as our recent investigations of condensed H2O, NH3, CH3CN, and CF3CH3. Auger electron photoion coincidence (AEPICO) spectra of condensed H2O at the O:1s ionization showed that H+ desorption was stimulated by O:KVV Auger processes leading to two - hole states (normal-Auger stimulated ion desorption (ASID) mechanism). The driving forces for H+ desorption were attributed to the electron missing in the O - H bonding orbitals and the effective hole-hole Coulomb repulsion. The normal ASID mechanism was also demonstrated for condensed NH3. The H+ desorption at the 4a1 ← O(N):1s resonance of both condensed H2O and condensed NH3 was found to be greatly enhanced. Based on the AEPICO spectra the following four-step mechanism was proposed: (1) the 4a1 ← 1s transition, (2) extension of the HO - H (H2N - H) distance within the lifetime of the (1s)-1(4a1)1 state, (3) spectator Auger transitions leading to (valence)-2(4a1)1 states, and (4) H+ desorption. The enhancement of the H+ desorption yield was attributed to therepulsive potential surface of the (1s) - 1(4a1)1 state. At the 3p ← O:1s resonance of condensed H2O, on the other hand, the H+ yield was found to be decreased. The AEPICO spectra showed that the H+ desorption was stimulated by spectator Auger transitions leading to (valence)-2(3p)1 states. The decrease in the H+ yield was attributed to a reduction in the effective hole-hole Coulomb repulsion due to shielding by the 3p electron. Photoelectron photoion coincidence (PEPICO) spectra of condensed H2O showed that the core level of the surface H2O responsible for the H+ desorption was shifted by 0.7 eV from that of the bulk H2O. The H+ desorption from condensed CH3CN was also investigated. In a study of condensed CF3CH3 using PEPICO spectroscopy, site-specific ion desorption was directly verified; that is, H+ and CH3+ desorption was predominant for the C:1s photoionization at the -CH3 site, while C2Hn+, CFCHm+, and CF3+ desorption was predominantly induced by the C:1s photoionization at the -CF3 site. These investigations demonstrate that EICO spectroscopy combined with synchrotron radiation is a powerful tool for studying PSID of molecules condensed at low temperature.